SUSTAINABLE DEVELOPMENT - ROY GHOSH M K (NEW DELHI ANE BOOKS PVT LTD, 2024)
"Sustainable Development: Environment, Energy and Water Resources" by Dr. M.K. Ghosh Roy. This book provides a comprehensive and technical examination of the challenges and potential solutions for achieving sustainability, focusing on the critical interlinked sectors of environment, energy, and water.
SUSTAINABLE DEVELOPMENT
ENVIRONMENTAL STUDIES
BTECH CIVIL
Keywords: ENVIRONMENTAL STUDIES; CIVIL ENGINEERING